Bioaccumulation of isocarbophos enantiomers from laboratory-contaminated aquatic environment by tubificid worms. (April 2015) - Liu, Tiantian; Diao, Jinling; Di, Shanshan; Zhou, Zhiqiang
Highlights: ICP's accumulation in tubificids was enantioselective in waterborne test. Dissipation patterns of ICP were different in the two sediments. Tubificids has a positive effect on diffusion of ICP from sediment to water. The level of accumulation was different in the two sediment treatments. For two sediments tests, different uptake ways dominate ICP' bioaccumulation. Abstract: The benthic fauna is of great importance to assess the environmental fate of contaminations in aquatic ecosystem. In this study, tubificids were exposed to both laboratory-contaminated aqueous phases and spiked sediment to study the bioaccumulation of isocarbophos (ICP). Two types of spiked sediments were used in the spiked sediment experiment. During the exposure period, an enantioselective bioaccumulation was found in spiked water treatment, with concentrations of the (−)-ICP higher than that of the (+)-ICP, but no enantioselectivity was detected in the spiked sediment treatments. However, different bioaccumulation patterns were observed in the two spiked sediment treatments. Results showed that for spiked forest field sediment (FF sediment) incubation, bioaccumulation was governed by the concentrations in soil. Whereas ICP was bioaccumulated dominantly from overlying water in spiked Chagan Lake sediment (CG sediment) test. The dissipation rates were proved different in the two sediments and ICP dissipated much faster in CG sediment than that in FF sediment. Significant difference in ICP's half-life was also observed between worm-present and worm-free treatments in FF sediment. The detections of concentrations in overlying water indicated that much more ICP diffused to aquatic phase with the present of tubificids.